2015
DOI: 10.1016/j.ijid.2015.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective study of risk factors for mortality in human avian influenza A(H7N9) cases in Zhejiang Province, China, March 2013 to June 2014

Abstract: Improvements in immunity, early case identification and treatment, and personal protection measures are key to addressing the high human avian influenza A(H7N9) case fatality rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…Activation of the complement system has been implicated in the development of acute lung diseases induced by highly pathogenic influenza viruses ( Garcia et al, 2013 , Sun et al, 2013 , Sun et al, 2015 ). Recent studies have brought up the idea of CRP to be not only a systemic marker of inflammation but also a mediator in inflammation faci ( Thiele et al, 2015 ), and indicated that high levels of CRP is a high risk factor of fatality in H7N9 patients ( Cheng et al, 2015 , Wu et al, 2016 ). However, its exact physiological roles remain largely unknown, especially in severe influenza diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Activation of the complement system has been implicated in the development of acute lung diseases induced by highly pathogenic influenza viruses ( Garcia et al, 2013 , Sun et al, 2013 , Sun et al, 2015 ). Recent studies have brought up the idea of CRP to be not only a systemic marker of inflammation but also a mediator in inflammation faci ( Thiele et al, 2015 ), and indicated that high levels of CRP is a high risk factor of fatality in H7N9 patients ( Cheng et al, 2015 , Wu et al, 2016 ). However, its exact physiological roles remain largely unknown, especially in severe influenza diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Research has indicated that a high viral load is associated with illness severity and prognosis, 24 which might have originated from poor hand hygiene and self-protection measures after contact with poultry or other animals. 13,25 To improve the survival of H7N9 VI, it is vital that appropriate hand hygiene practices are implemented by the susceptible population after direct contact with poultry or birds. Furthermore, it can be inferred that PHH is associated with a nonlinear effect on the survival of H7N9 patients (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the investigators present their results with 95% confidence interval (CI), Z 0:05 =1.96 (α= 0.05), Z 0:10 =1.64 (β= 0.10), r = 2, p 0 = 35.3%, and OR= 2.5. 13 In addition, considering the loss of follow-up, participants' rejection rate, and sampling error, the final sample size was determined to be 200 in the training set. The validation set was selected in this study using the 'all comers' design.…”
Section: Sample Size Calculationmentioning
confidence: 99%
See 2 more Smart Citations